2012
DOI: 10.1007/s10531-012-0258-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agri-environment management for cirl buntings on other biodiversity

Abstract: Agri-environment scheme (AES) management has increased populations of cirl buntings (Emberiza cirlus) in South Devon, England, and might be expected to provide benefits for other declining biodiversity, due to less intensive farm management. Fields managed under AES for cirl buntings (low-input spring barley or permanent pasture without inputs) were contrasted with control fields under conventional management (spring barley without management restrictions and winter cereals, or grazed without management restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…This study provides strong evidence of the value of targeted AESs in improving habitat conditions of non-target species as suggested by other studies ( MacDonald et al, 2012a , b ; Wilkinson et al, 2012 ; Helden et al, 2015 ). While the conservation of moths in farmland may require specific tailored management actions (but see Merckx et al, 2010b ), our findings indicate that moths may also benefit from sympathetic hedgerow management targeting R. ferrumequinum , a bat species of major conservation concerns.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study provides strong evidence of the value of targeted AESs in improving habitat conditions of non-target species as suggested by other studies ( MacDonald et al, 2012a , b ; Wilkinson et al, 2012 ; Helden et al, 2015 ). While the conservation of moths in farmland may require specific tailored management actions (but see Merckx et al, 2010b ), our findings indicate that moths may also benefit from sympathetic hedgerow management targeting R. ferrumequinum , a bat species of major conservation concerns.…”
Section: Discussionsupporting
confidence: 83%
“…Because HLS prescriptions were implemented in targeted high-priority areas where the most threatened farmland species occur ( Natural England, 2013b ), we conducted our study on farms where sympathetic hedgerow management was mainly carried out to enhance greater horseshoe bat ( Rhinolophus ferrumequinum ) populations. Hence, this study design also allowed us to assess whether a targeted AES that mainly focused on a single threatened species may have wider biodiversity benefits as suggested by other studies ( MacDonald et al, 2012a , b ; Wilkinson et al, 2012 ; Helden et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, results diverged according to studies, showing significantly positive effects of organic farming compared to conventional farming on activity (Fuller et al., ; Wickramasinghe, Harris, Jones, & Jennings, ; Wickramasinghe, Harris, Jones, & Vaughan, ), species richness, and diversity (Fuller et al., ). It was also found that there were no differences (Pocock & Jennings, ) but driven differences in boundaries between organic and conventional, as well as two cases of significant negative effect on diversity (Fuller et al., ) and activity (MacDonald et al., ). In all these studies, the activity of strictly insectivorous bats was measured during their foraging activity, known to be driven by arthropod availability (Charbonnier, Barbaro, Theillout, & Jactel, ; Hayes, ).…”
Section: Introductionmentioning
confidence: 96%
“…Several species identified as threatened by the International Union for Conservation of Nature are largely affected by intensive agriculture (Azam, Le Viol, Julien, Bas, & Kerbiriou, 2016). Moreover, AES do not seem to encourage conservation of such species in conventional farming (Fuentes-Montemayor, Goulson, & Park, 2011;MacDonald et al, 2012;Park, 2015) even having negative effects sometimes (Fuentes-Montemayor et al, 2011) that accentuate the urgent need to assess the effects of farming practices.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, by 1989 it was largely restricted to a small area of south Devon (Sitters, ; Evans, ; Wotton et al ., ). Concern for the species' survival at the national level gave rise to a programme of research into its ecological requirements, which led to the development of a special option within the Countryside Stewardship Scheme in 1993 (one of the AES schemes operating within England at that time) specifically to reverse the decline in the cirl bunting population (Jeffs & Evans, ; MacDonald et al ., ). Since 1993 there has been a considerable reversal of fortune, with an increase in the breeding population from a probable 118 pairs in 1989 to an estimated 862 pairs in 2009 (Evans, ; Davies et al ., ).…”
Section: Introductionmentioning
confidence: 97%